Dynamics of a True Moving Bed separation process: Effect of operating variables on performance indicators using orthogonalization method - Ildefonso B. R Nogueira (2016)
The assessment of the performance of cyclic adsorption systems is usually addressed in literature in terms of steady state. To reach further developments in this field, the characterization of the dynamic behavior of the processes becomes necessary. This work focus on the application of a method based on Gram-Schmidt Orthogonalization to analyze the impact of the operating variables in the dynamic response of a TMB unit. Another objective of this work is to characterize the dynamic system behavior and compare it with the orthogonalization method results. The results showed that the recycling flow rate is the operating variable with the greatest impact for the system considered. The step perturbation analysis showed the consistence of the proposed method and that some process variables result in a system inverse response for the recovery performance indicator. The importance of taking in consideration the process dynamics in the unit design, control and optimization is demonstrated.